Community Resilience and Well-Being: An Exploration of Relationality and Belonging after Disasters. Issue 2 (21st August 2020) - Quinn, Tara; Adger, W. Neil; Butler, Catherine; Walker-Springett, Kate
Abstract : Community resilience is commonly held to be critical for coping with adversity and disturbance. Although the process of community resilience is often contested and critiqued, the enactment of social relations within communities has been shown to ameliorate the worst impacts of disaster events on the well-being of their members. Here, we propose that well-being in the aftermath of disasters is shaped by processes of relationality and belonging within communities. This study uses data from longitudinal mixed-methods research with flood-affected communities in southwest and eastern England directly affected by long-duration and high-impact floods. Analysis from in-depth interviews conducted over eighteen months and from cross-sectional surveys of affected populations shows that active belonging and relational capital are related to self-reported well-being. The results further show that active belonging is consistently significant for well-being, whereas relational capital is only significantly correlated to well-being later in the recovery period, and that social identity processes are central in the link between community dynamics and well-being. The changing identity processes include altered perceptions of community membership and the use of collective identities to frame personal experience. These results suggest that community resilience processes and their relationship to individual well-being are not fixed but evolve through stress, trauma, and renewal.